Storied and Supernatural Places Studies in Spatial and Social Dimensions of Folklore and Sagas - Valk, Ülo; Sävborg, Daniel (Studia Fennica Folkloristica, 2018)
"This book addresses the narrative construction of places, the relationship between tradition communities and their environments, the supernatural dimensions of cultural landscapes and wilderness as they are manifested in European folklore and in early literary sources, such as the Old Norse sagas. The first section "Explorations in Place-Lore" discusses cursed and sacred places, churches, graveyards, haunted houses, cemeteries, grave mounds, hill forts, and other tradition dominants in the micro-geography of the Nordic and Baltic countries, both retrospectively and from synchronous perspectives. The supernaturalisation of places appears as a socially embedded set of practices that involves storytelling and ritual behaviour. Articles show, how places accumulate meanings as they are layered by stories and how this shared knowledge about environments can actualise in personal experiences. Articles in the second section "Regional Variation, Environment and Spatial Dimensions" address ecotypes, milieu-morphological adaptation in Nordic and Baltic-Finnic folklores, and the active role of tradition bearers in shaping beliefs about nature as well as attitudes towards the environment. The meaning of places and spatial distance as the marker of otherness and sacrality in Old Norse sagas is also discussed here. The third section of the book "Traditions and Histories Reconsidered" addresses major developments within the European social histories and mentalities. It scrutinizes the history of folkloristics, its geopolitical dimensions and its connection with nation building, as well as looking at constructions of the concepts Baltic, Nordic and Celtic. It also sheds light on the social base of folklore and examines vernacular views toward legendry and the supernatural."